Real-world evaluation of health-related quality of life in patients with diffuse large B-cell lymphoma based on a multinational survey - Johnson, P. Connor; Bailey, Abigail; Ma, Qiufei; Milloy, Neil; Butcher, Jake; Sanderson, Isaac; Weatherby, Sarah; Meadows, Rachael; Quek, Ruben G. W. (Frontiers in Oncology, 2024)
Background: Real-world health-related quality of life (HRQoL) data in patients with diffuse large B-cell lymphoma (DLBCL) are scarce. This study is to compare patient-reported outcomes in patients with DLBCL across therapy lines and countries. Methods: Data were derived from the Adelphi DLBCL Disease Specific Programme™ from January 2021 to May 2021, a survey of physicians and their DLBCL patients in France, Germany, Italy, Spain, United Kingdom (UK), and the United States (US). Results: Overall, analysis was conducted on 441 patients with DLBCL across Europe and the US (mean age 64.6 years, 64% male); 68% had an Ann Arbor stage III and 69% had an Eastern Cooperative Oncology Group Performance Status of 0 to 1. The mean overall GHS/QoL was 54.1; patients on their 3L+ therapy had a lower mean GHS/QoL compared with patients on 1L/2L (P = 0.0033). Further to this, mean EQ-5D-5L utility score was reduced from 0.73 for patients on 1L therapy to 0.66 for patients on 3L+ therapies (P = 0.0149). Mean percentages of impairment while working and overall work impairment were lower for patients receiving 3L+ therapy (12.5% and 17.7%; respectively) than those on 1L therapy (35.6 % and 33.8%; respectively). When comparing region, patients in the US had significantly better scores for all functioning and symptomatic scales (per EORTC QLQ-C30). and work impairment (per WPAI) vs. patients with DLBCL in Europe. WPAI scores indicate that the overall activity impairment in the US was 36.6% and in Europe ranged from 42.4% in the UK to 54.9% in Germany. Mean EQ-5D-5L utility score for the US was 0.80, compared to 0.60 – 0.80 across the countries in Europe. Regression analysis showed patients who relapsed after more than one year of treatment were associated with better patient reported outcomes than those who relapse after less than one year. Conclusion: Patient-reported outcomes of DLBCL patients remain poor and patients continue to experience considerable morbidity.